Digital Leadership: Navigating the Future with Strategic Conviction - Baqer Khudair Al-Hadrawi; Reniati Reniati (International Journal of Magistravitae Management, 2023)
This theoretical study delves into the concept of Digital Leadership, exploring its intricacies and relevance in navigating the future with strategic conviction. As organizations grapple with the rapidly evolving digital landscape, effective leadership becomes paramount. The abstract dissects the theoretical framework of Digital Leadership, unraveling its core components and their implications for organizational success. Emphasizing the fusion of technology acumen and strategic foresight, the study proposes a model for leaders to navigate the complexities of the digital era adeptly. Through an in-depth analysis, it elucidates the role of strategic conviction in shaping digital leadership, positing that visionary decision-making is crucial for capitalizing on emerging opportunities and mitigating challenges. By synthesizing established leadership theories with contemporary digital insights, this study contributes to a nuanced understanding of the theoretical foundations underpinning Digital Leadership, offering a roadmap for leaders to proactively steer their organizations toward sustainable success in an ever-evolving digital landscape.